Antimicrobial effects of colloidal silver washes against Salmonella and Escherichia coli O157:H7 on fresh beef - Coger, R.R.; Franken, L.J.; Herald, T.; Phebus, Randall K.; Marsden, James L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Beef carcasses and fresh fabricated beef products potentially can be contaminated with disease causing microorganisms (pathogens) via animal dressing procedures and contamination from the plant environment or workers. Concentrated efforts have been made by the meat industry to develop and implement a wide array of strategies to control such contamination. Spraying beef flank (Rectus abdominus) samples with 32 ppm colloidal silver (ASAP®, American Biotech Labs) solution for 20 seconds reduced Salmonella and Escherichia coli O157:H7 numbers by greater than 90% after 4 hours. Inoculated samples treated with 22 ppm colloidal silver, 22 ppm colloidal silver plus 1.5% hydrogen peroxide, 10 ppm colloidal silver, or 10 ppm colloidal silver plus potassium persulfate had moderate to slight pathogen reductions compared with those treated with 32 ppm colloidal silver. Although not yet approved for use on foods (but approved for other human health applications), a colloidal silver rinse implemented in conjunction with other antimicrobial intervention technologies during the beef carcass conversion and/or fabrication processes could be an effective strategy against Salmonella and E. coli O157:H7. Further studies should be conducted on colloidal silver’s antimicrobial effectiveness on lean tissues versus adipose tissue, and on sensory and functional effects on fresh meat products during storage.
Keywords: Beef; Colloidal silver washes; Salmonella; Escherichia coli O157:H7